Genome-Wide Identification, Expression Profiling, and Evolution of Phosphate Transporter Gene Family in Green Algae - Wang, Long; Xiao, Liang; Yang, Haiyan; Chen, Guanglei; Zeng, Houqing; Zhao, Hongyu; Zhu, Yiyong (Frontiers in Genetics, 2020)
Phosphorus (P) is an essential nutrient for plant growth and development. Phosphate transporters (PHTs) are trans-membrane proteins, that mediate the uptake and translocation of Pi in green plants. PHT family, including PHT1, PHT2, PHT3 and PHT4 subfamily, are well-studied in land plants, however, PHT genes in green algae are poorly documented and not comprehensively identified. Here we analyzed the PHTs in a model green alga Chlamydomonas reinhardtii and found 25 putative PHT genes, which can be divided into four subfamilies. The subfamilies of CrPTA, CrPTB, CrPHT3 and CrPHT4 contains four, eleven, one and ninegenes, respectively. The structure, chromosomal distribution, localization, duplication, phylogenies and motifs of these genes were systematically analyzed in silico. Expression profiles analysis showed that CrPHT genes displayed differential expression patterns under P starvation condition. The expression levels of CrPTA1 and CrPTA3 were down-regulated, while the expression of most PTB genes was up-regulated under P starvation, which may be controlled by CrPSR1. The transcript abundance of most PHT3 and PHT4 genes was not signiﬁcantly affected by P starvation except PHT4-3, PHT4-4 and PHT4-6. Our results provided a basic information for understanding evolution and features of the PHT family in green algae.